Effects of doxazosin as adjuvant to abiraterone on viability and apoptosis of metastatic castration-resistant prostate cells cancer (mCRPC) PC3 - Pratama, Putu KD.; Rahman, Zakaria A.; Hidayatullah, Furqan; Laksita, Tetuka B.; Hakim, Lukman (Narra J, 2025)
Prostate cancer is a leading cause of death among men worldwide, with limited therapeutic options for castration-resistant metastatic prostate cancer (mCRPC). The aim of this study was to investigate the potential role of doxazosin, an α1-blocker, as an adjunctive therapy for mCRPC in combination with abiraterone. Using mCRPC PC3 cells, the effects of doxazosin on cell viability and apoptosis were assessed. The experimental design was an in vitro study with post-test-only control design. Experimental groups were divided into four groups: control group, doxazosin group, abiraterone group, and combination group (doxazosin and abiraterone). Cell viability was analyzed using the cell counting kit-8 (CCK-8) assay, while apoptosis was analyzed using Fluorescence-activated cell sorting (FACS). This study found that the IC50 value for doxazosin was 25.42±1.42 µM (mean ± standard error). The results indicated that doxazosin significantly reduced cell viability, with effects varying based on the dose administered, and doxazosin was able to induce apoptosis in mCRPC PC3 cells. The combined treatment of doxazosin and abiraterone in mCRPC PC3 cells demonstrated a significantly higher mean apoptosis percentage compared to the control group (16.27%; 95% confidence interval (CI): 11.89–20.65; p=0.001). Furthermore, the combined treatment showed a significantly higher mean apoptosis percentage compared to abiraterone alone (4.79%; 95%CI: 0.41–9.18; p=0.029), and doxazosin alone (10.99%; 95%CI: 6.61–15.38; p=0.001). These findings suggest that doxazosin, traditionally used as an α1-blocker for lower urinary tract symptoms (LUTS), could offer a novel therapeutic approach for mCRPC patients.